Analisis Pengaruh Disiplin Kerja Dan Kompensasi Finansial Terhadap Produktivitas Kerja Karyawan PT XYZ - Samuel Kurniawan Sutiono; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research aims to determine the influence of work discipline and financial compensation on employees’ productivity and performance at the PT XYZ plant office in Bekasi, West Java. This research itself can be calculated. The sample taken was 40 respondents using a purposive sampling technique. The measuring instrument used is a questionnaire shared and spreaded via google form. The data in this research were analyzed using SPSS 22. From the results of the analysis of the hypothesis that; Work discipline has a notable effect on employee work productivity, financial compensation does not have a significant effect on employee work productivity, while the results of the f-test for the three variables effect simultaneously